Early coagulation support protocol: A valid approach in real-life management of major trauma patients. Results from two Italian centres. Issue 10 (October 2019) - Bocci, Maria Grazia; Nardi, Giuseppe; Veronesi, Giovanni; Rondinelli, Maria Beatrice; Palma, Antonella; Fiore, Valentina; De Candia, Erica; Bianchi, Maria; Maresca, Maddalena; Barelli, Roberta; Tersali, Alessandra; Dell'Anna, Antonio Maria; et al.
Highlights: The ECS protocol reduces blood product consumption and it may be adopted in real-life management of major trauma patients. The application of the ECS protocol, compared to a plasma-based strategy, is associated with a reduction in hospital length of stay. The ECS protocol provides the early infusion of tranexamic acid, fibrinogen concentrate and pRBC, instead of FFP for early coagulopathy support. The application of the ECS protocol guarantees early coagulation support in major trauma patients with high bleeding risk. Abstract: Introduction: Early coagulation support (ECS) includes prompt infusion of tranexamic acid, fibrinogen concentrate, and packed red blood cells for initial resuscitation of major trauma patients. The aim of this study was to determine the effects, in terms of blood product consumption, length of stay, and in-hospital mortality, of the ECS protocol, compared to the massive transfusion protocol (MTP) in the treatment of major trauma patients. Patients and methods: A retrospective analysis was conducted using the registry data of two Italian trauma centres. Adult major trauma patients with, or at risk of, active bleeding who were managed according to the MTP during the years 2011–2012, or the ECS protocol during the years 2013–2014 and were considered at risk of multiple transfusions, were enrolled. The primary endpoint was to determine whether the ECS protocol reduces the use of blood products in the acute management of trauma patients. Secondary endpoints were the outcome measures of length of stay in ICU, length of stay in hospital, and mortality at 24-hours and 28-days after hospital admission. Results: Among the 518 major trauma patients admitted to the trauma centres during the study period, 235 patients (118 in the pre-ECS period and 117 in the ECS period) matched one of the inclusion criteria and were enrolled in the study. Compared with the pre-ECS period, the ECS period showed a reduction in the average consumption of packed red blood cells (−1.87 units, 95% confidence interval [CI], −2.40, −1.34), platelets (−1.28 units; 95% CI, −1.64, −0.91), and fresh frozen plasma (−1.69; 95% CI, −2.14, −1.25) in the first 24-hours. Furthermore, during the ECS period, we recorded a 10-day reduction in the hospital length of stay (−10 days, 95% CI, −11.6, −8.4) and a non-significant 28-day mortality increase. Conclusions: The ECS protocol was effective in reducing blood product consumption compared to the MTP and confirmed the importance of early fibrinogen administration as a strategy of rapid coagulation. This novel approach may be adopted in real-life management of major trauma patients.